A New Antisense Phosphoryl Guanidine Oligo-2′-O-Methylribonucleotide Penetrates Into Intracellular Mycobacteria and Suppresses Target Gene Expression - Skvortsova, Yulia V.; Salina, Elena G.; Burakova, Ekaterina A.; Bychenko, Oksana S.; Stetsenko, Dmitry A.; Azhikina, Tatyana L. (Frontiers in Pharmacology, 2019)
The worldwide spread of multidrug resistant Mycobacterium tuberculosis strains prompted the development of new strategies to combat tuberculosis, one of which is antisense therapy based on targeting bacterial mRNA by oligonucleotide derivatives. However, the main limitation of antisense antibacterials is poor cellular uptake because of electrostatic charge. Phosphoryl guanidine oligo-2’-O-methylribonucleotides (2’-OMe PGO) are a novel type of uncharged RNA analogues with high RNA affinity, which penetrate through the bacterial cell wall more efficiently. In this study, we investigated the uptake and biological effects of 2’-OMe PGO in mycobacteria. The results indicated that 2’-OMe PGO specific for the alanine dehydrogenase-encoding ald gene inhibited the growth of M. smegmatis and downregulated ald expression both at the transcriptional and translational level through an RNase H-independent mechanism, showing higher biological activity than its phosphorothioate oligonucleotide counterpart. Confocal microscopy revealed that the anti-ald 2’-OMe PGO was taken up by intracellular mycobacteria residing in RAW 264.7 macrophages without exerting toxic effects on eukaryotic cells, indicating that 2’-OMe PGO was able to efficiently cross two cellular membranes. In addition, 2’-OMe PGO inhibited the transcription of the target ald gene in M. smegmatis-infected macrophages. Thus, we demonstrated, for the first time, a possibility of targeting gene expression and inhibiting growth of intracellular mycobacteria by antisense oligonucleotide derivatives. Strong antisense activity and efficient uptake of the new RNA analogue, 2’-OMe PGO, by intracellular microorganisms revealed here may promote the development of novel therapeutic strategies to treat TB and prevent the emergence of drug-resistant mycobacterial strains.